Analysis of Trends in Scientific Publication Topics for Lecturers in the Department of Computer Engineering and Informatics, Medan State Polytechnic Using Co-Words Analysis - Munthe, Hamzah Syahbana; Handoko, Riki (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Research in the pertinent subject is a key component in the advancement of science. This was carried out in an effort to address a number of issues and broaden the body of knowledge in this scientific domain. In Indonesia, academics, practitioners, and researchers hold seminars hosted by government and non-government organizations with the goal of giving them a platform to enhance scientific articles by offering corrections to their findings. Papers, theses, dissertations, and scientific journals were the primary sources of information for earlier bibliometric scholars. This is done in order to observe information utilization, gathering, obsolescence, knowledge mapping, etc. The background information for this research is as follows, based on the material above: first, there is no knowledge mapping to identify trends in research topics, particularly in computer science-related scientific articles, particularly in the Department of Computer Engineering and Informatics at Medan State Polytechnic. The problem to be researched will be formulated using numerical measuring instruments based on trends in research topics and bibliometric studies of scientific articles in proceedings in the field of computer and information science at seminars and conferences in Indonesia.